PREDICTING THE FINANCIAL FAILURE OF COMMERCIAL BANKS USING THE KIDA MODEL AND SHERROD MODEL. (AN ANALYTICAL STUDY IN A NUMBER OF IRAQI COMMERCIAL ( )BANKS) - Lecturer. Dr. Wisam Sami Jabbar Zinal (Scholar Express Journals, 2023)
The research aims to shed light on the financial failure that commercial banks may experience at the end of their financial decline stages as a result of their exposure to various and sequential financial risks, starting with the risk of liquidity and ending with the risk of bankruptcy and liquidation. Among these models are the Kida model and the Sherrod model. The research reached a set of conclusions, the most important of which is that all commercial banks are in the research sample listed in the Iraq Stock Exchange, according to the models (Kida) and (Sherrod), in the case of safety from financial failure, except for the Bank of Baghdad, the United Bank for Investment, and the Mansour Investment Bank, which are threatened with financial failure.
Keywords: Financial failure; model